Boganmeldelser - Jareborg, Nils; Bratholm, Anders; Felson, Marcus; Weber, Hartmut-Michael; Soothill, Keith; Lane, Roger; Finckenauer, James O.; Waring, Elin J.; Basberg, Cecilie E. (Nordisk Tidsskrift for Kriminalvidenskab, 2000)
Intet resumé